ESTERIFIKASI 2-ISOPROPIL-5-METILSIKLOHEKSANOL (l-MENTOL) MENGGUNAKAN ASAM PROPIONAT - Retnowati, Rurini; Suratmo, Suratmo; Nurita, Friska Devi Mella (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Menthol is one of peppermint oil components (Mentha piperita). It can be converted into menthyl propionate that have stronger aroma than alcohol compounds. The aims of this research were to synthesize ester l-menthyl propionate using l-menthol and propionate acid and study on the influence of mole ratio of reactans to esters product. The esterifications were carried out by reacting l-menthol and propionate acid in ether solvents and sulfuric acid as catalyst. The mixture was refluxed for 1 hour. The ratio of l-menthol and propionate acid were set at 1:1, 1:2, 1:3, 1:4. The products of esterification were characterized based on physical properties (color and odor) and analyzed by TLC, GC, GC-MS and FT-IR Spectrophotometry. The result of characterization showed that the products are a mixture of l-menthol and l-menthyl propionate. This products have a yellow color and stronger aroma than l-menthol. The results showed the highest yield of synthesis products 22.5 % was obtained at mole ratio l-menthol:propionate acid 1:1. Key words: esterification, l-menthyl propionate, mole ratio